Analysis of the political content and impact on public opinion in the city of Guayaquil - Chica Pincay, José; Trujillo Maldonado, Gabriela (Revista Universidad de Guayaquil, 2022)
The present research is non-experimental-transectional because it does not test or modify any of the study variables, in other words, the facts have already occurred. It is transitional because it collects data from the Bellavista’s citadel in the city of Guayaquil. The methodology used was the nonexperimental design, at the level of descriptive and field study, using quali-quantitative approach. The data collection technique was a non-probabilistic survey of one hundred people from the Bellavista citadel in order to establish the effect of public opinion. Therefore, the study carried out on the digital medium is framed in a recursive point of view, where the media impact is filtered as an expression of common thought among citizens, however, everyone has access to information, not only to the internet, but also to mobile phones or web news portals, available resources that make verification a relevant exercise. That is, it is necessary that online information through digital media is truthful and contrasted. It is evident that a content analysis is required to the main cybermedia in social networks to know how they contribute to media representation.